A high energy storage sodium niobate-based high entropy ceramic material and its preparation method and application

By introducing high entropy components (La0.2Nd0.2Sm0.2Gd0.2Bi0.2)(Mg2/3Nb1/3)O3 in NaNbO3, the shortcomings of existing lead-free ceramic materials in energy storage density and efficiency are solved, and the energy storage density and efficiency of the existing lead-free ceramic materials are achieved. Ceramic materials with high energy storage density and high energy storage efficiency are suitable for the application of multilayer capacitors.

CN117819964BActive Publication Date: 2025-02-18SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311690566.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-11
Publication Date
2025-02-18
Estimated Expiration
2043-12-11

AI Technical Summary

Technical Problem

The existing lead-free ceramic materials have shortcomings in energy storage density and efficiency, and it is difficult to achieve high energy storage density and high energy storage efficiency at the same time, which limits its application in pulse power systems.

Method used

By introducing high-entropy components (La0.2Nd0.2Sm0.2Gd0.2Bi0.2)(Mg2/3Nb1/3)O3 in NaNbO3, the local structure disorder and reduction are enhanced by using the hysteresis diffusion effect and lattice distortion effect. Grain size, thereby improving the energy storage characteristics of ceramic materials.

Benefits of technology

It achieves high energy storage density (maximum 4.48J/cm3) and high energy storage efficiency (maximum 88.2%), which is suitable for the preparation and application of multilayer capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117819964B_ABST
    Figure CN117819964B_ABST
Patent Text Reader

Abstract

The present invention relates to a high-energy storage sodium niobate-based high-entropy ceramic material and a preparation method and application thereof. The chemical molecular formula of the high-energy storage sodium niobate-based high-entropy ceramic material is (1-x)NaNbO3-x(La 0.2 Nd 0.2 Sm 0.2 G 0.2 Bi 0.2 )(Mg 2 / 3 Nb 1 / 3 )O3; where 0.01≤x≤0.09.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a sodium niobate-based high-entropy ceramic material with high energy storage characteristics and a preparation method and application thereof, belonging to the technical field of functional ceramics. Background Art

[0002] Energy storage components play an important role in modern civilized life. Among them, dielectric energy storage technology has a very fast charge and discharge rate (~μs) and power density (10 4 ~10 5 W / kg), and has been widely used in pulse power supplies, power devices, and electronic equipment. The use of traditional lead-based energy storage ceramics has been restricted by various countries due to the serious harm to nature and human bodies in the process of raw material mining, device preparation, and recycling. The low energy storage density of lead-free dielectric materials currently poses a huge challenge to the integration, lightweight, and miniaturization of pulse power systems. Therefore, it is urgent to develop lead-free ceramic materials with high energy storage density.

[0003] NaNbO3(NN) is a lead-free antiferroelectric material with rich temperature-induced phase transitions and extremely small antiferroelectric-ferroelectric free energy difference. s Larger (about 40μC / cm 2 ), a high bandgap (3.58eV) and a special irreversible antiferroelectric-ferroelectric phase transition under an electric field, which has attracted widespread attention and is considered to be a very promising dielectric energy storage material. The relaxation engineering of ferroelectric and antiferroelectric materials has a significant effect on reducing their polarization hysteresis and phase transition hysteresis under an electric field, so it is widely used as a control method to improve the energy storage performance of ferroelectric / antiferroelectric ceramics.

[0004] Chinese patent (publication number CN110204335A) adds (Bi 0.5 Na 0.5 )HfO3, increasing the energy storage efficiency to 3.51J / cm 3 , while the energy storage efficiency reaches more than 80%. Chinese Patent 2 (Publication No. CN109809815A) prepared NaNbO3-CaSnO3 lead-free sodium niobate-based antiferroelectric ceramics with high saturation polarization and low residual polarization. Although a lot of research has been done on lead-free ceramics, most single-structure lead-free ceramics currently have difficulty in achieving high energy storage density and energy storage efficiency at the same time, so it is necessary to try other modification methods to further explore its energy storage characteristics.

[0005] The design idea of ​​"high entropy" originated from alloy materials. As early as the 1980s, Professor B. Cantor's team discovered a single-phase alloy CrMnFeCoNi formed by solid solution of five metals in equal proportions based on the face-centered cubic structure, and once called it "Cantor aluminum alloy"; subsequently, the research team of National Tsing Hua University in Taiwan also reported the alloy MoTiVFeNiZr formed by mixing multiple metal elements in equal proportions, thus opening the door to "high entropy alloys". In the process of systematic research on high entropy alloys, researchers have summarized its four unique effects: ① high entropy effect, ② hysteresis diffusion effect, ③ lattice distortion effect, and ④ "cocktail" effect. Among them, the hysteresis diffusion effect refers to the interaction between the various elements in the material matrix, which leads to a significant reduction in the diffusion effect of various atoms; the lattice distortion effect refers to the irregular distortion or torsion of the lattice caused by the random substitution of atoms of various different radii in the lattice, thereby causing changes in macroscopic properties. The Chinese patent (publication number: CN115991599A) introduces the B-site high entropy component Bi (Zn 0.2 Mg 0.2 Al 0.2 Mn 0.2 Hf 0.2 )O3, successfully prepared high entropy perovskite oxide doped ceramics, but its energy storage properties are still far from practical application. Chinese patent (publication number: CN114956809A) in the high entropy component (Na 0.2 Bi 0.2 Ba 0.2 Sr 0.2 Ca 0.2 )TiO3 doped with a small amount of NaNbO3 obtained an energy storage density of 3.51 J / cm 3 , a ceramic material with an energy storage efficiency of 77.7%, but the lower energy storage density and efficiency limit its further application. Therefore, it is necessary to develop a new type of high energy storage sodium niobate-based high entropy ceramic material. Summary of the invention

[0006] In view of the above problems, the purpose of the present invention is to utilize the characteristics of "hysteresis diffusion effect" and "lattice distortion effect" among the four major effects of high entropy compounds to enhance the local structural disorder and reduce the grain size. The present invention provides a sodium niobate-based high entropy ceramic material with high energy storage, a preparation method and application thereof.

[0007] In a first aspect, the present invention provides a high energy storage sodium niobate-based high entropy ceramic material, wherein the chemical formula of the high energy storage sodium niobate-based high entropy ceramic material is (1-x)NaNbO3-x(La 0.2 Nd 0.2 Sm 0.2 G 0.2 Bi0.2 )(Mg 2 / 3 Nb 1 / 3 )O3; where 0.01≤x≤0.09.

[0008] In the present invention, a specific amount of high entropy component (La 0.2 Nd 0.2 Sm 0.2 G 0.2 Bi 0.2 )(Mg 2 / 3 Nb 1 / 3 )O3 obtained a ceramic material with excellent energy storage characteristics and electrical properties.

[0009] Preferably, 0.03≤x≤0.09, preferably 0.05≤x≤0.07.

[0010] Preferably, the breakdown electric field of the high energy storage sodium niobate-based high entropy ceramic material is tested by a TFAnalyzer 2000E ferroelectric analyzer to be 248 to 432 kV / cm, preferably 300 to 432 kV / cm;

[0011] The energy storage efficiency of the high energy storage sodium niobate-based high entropy ceramic material is tested by using a TFAnalyzer 2000E ferroelectric analyzer and is 24.5-88.2%;

[0012] The energy storage density of the high energy storage sodium niobate-based high entropy ceramic material was tested by TFAnalyzer 2000E ferroelectric analyzer and was 1.66-4.48 J / cm 3 , preferably 2.78 to 4.48 J / cm 3 .

[0013] In a second aspect, the present invention provides a method for preparing a high energy storage sodium niobate-based high entropy ceramic material, comprising:

[0014] (1) Sodium carbonate powder, niobium pentoxide powder, lanthanum oxide powder, neodymium oxide powder, gadolinium oxide powder, samarium oxide powder, bismuth oxide powder and magnesium oxide powder are selected as raw materials and prepared according to the chemical formula (1-x)NaNbO3-x(La 0.2 Nd 0.2 Sm 0.2 G 0.2 Bi 0.2 )(Mg 2 / 3 Nb 1 / 3 )O3 is weighed and mixed, and then calcined to obtain ceramic powder;

[0015] (2) mixing the obtained ceramic powders, adding a binder, and granulating, sieving and molding to obtain a ceramic green body;

[0016] (3) After the obtained ceramic green body is molded, it is sintered at 1300-1320° C. for 2-3 hours to obtain the high energy storage sodium niobate-based high entropy ceramic material.

[0017] Preferably, in step (1), the mixing method is ball milling; the rotation speed of the ball milling is 200-240 rpm, and the time is 4-6 hours; the calcination temperature is 850-950° C., and the time is 4-5 hours.

[0018] Preferably, in step (2), the binder is a polyvinyl alcohol aqueous solution with a concentration of 6 to 7 wt.%; the amount of the binder added is 6 to 7 wt.% of the mass of the ceramic powder; and the sieve is 40 mesh.

[0019] Preferably, in step (3), the temperature of the plastic discharge is 750-850°C, and the time is 2-3 hours; preferably, the temperature of the plastic discharge is 800°C, and the time is 2 hours;

[0020] The heating rate of the sintering is 1-3°C / min, preferably 2°C / min.

[0021] In a third aspect, the present invention provides an energy storage ceramic element, comprising: a high energy storage sodium niobate-based high entropy ceramic material, and electrodes distributed on the surface of the sodium niobate-based ceramic material.

[0022] In a fourth aspect, the present invention provides an application of a high-energy storage sodium niobate-based high-entropy ceramic material in a multilayer ceramic capacitor (Multi-Layer Ceramic Capacitor, MLCC).

[0023] Beneficial effects of the present invention:

[0024] In the present invention, the obtained sodium niobate-based high entropy ceramic material has the characteristics of excellent temperature stability, high breakdown strength, high energy storage density, etc. The present invention has a simple preparation process, can work in extreme environments, and is suitable for the preparation and application of multilayer capacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is an X-ray diffraction pattern of the sodium niobate-based ceramic material prepared in Example 1-4;

[0026] Figure 2 is a surface microscopic morphology of the sodium niobate-based ceramic material in Example 1;

[0027] Figure 3 is a surface microscopic morphology of the sodium niobate-based ceramic material in Example 2;

[0028] Figure 4is a surface microscopic morphology of the sodium niobate-based ceramic material in Example 3;

[0029] Figure 5 is a surface microscopic morphology of the sodium niobate-based ceramic material in Example 4;

[0030] Figure 6 is the dielectric temperature spectrum of the sodium niobate ceramic material in Example 1;

[0031] Figure 7 is the dielectric temperature spectrum of the sodium niobate-based ceramic material in Example 2;

[0032] Figure 8 This is the dielectric temperature spectrum of the sodium niobate-based ceramic material in Example 3.

[0033] Fig. 9 The dielectric temperature spectrum of the sodium niobate-based ceramic material in Example 4 is

[0034] Fig.10 is a unipolar hysteresis loop diagram of the sodium niobate-based ceramic material in Example 1;

[0035] Fig.11 is a unipolar hysteresis loop diagram of the sodium niobate-based ceramic material in Example 2;

[0036] Fig.12 is a unipolar hysteresis loop diagram of the sodium niobate-based ceramic material in Example 3;

[0037] Fig.13 is a unipolar hysteresis loop diagram of the sodium niobate-based ceramic material in Example 4;

[0038] Fig.14 is a graph showing changes in energy storage density and energy storage efficiency of sodium niobate-based ceramic materials in Examples 1-4;

[0039] Fig.15 is a unipolar hysteresis loop diagram of the sodium niobate-based ceramic material at different frequencies in Example 2;

[0040] Fig.16 is a graph showing changes in energy storage density and energy storage efficiency of the sodium niobate-based ceramic material at different frequencies in Example 2;

[0041] Fig.17 is a unipolar hysteresis loop diagram of the sodium niobate-based ceramic material at different cycle times in Example 2;

[0042] Fig.18 The energy storage density and energy storage efficiency of the sodium niobate-based ceramic material under different cycle times in Example 2 are shown in FIG. DETAILED DESCRIPTION

[0043] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0044] In the present invention, the chemical formula of the sodium niobate-based ceramic material is (1-x)NaNbO3-x(La 0.2 Nd 0.2 Sm 0.2 G 0.2 Bi 0.2 )(Mg 2 / 3 Nb 1 / 3 )O3. Wherein x = 0.03 to 0.09.

[0045] Preferably, x=0.07.

[0046] In the present invention, the obtained sodium niobate-based ceramic material has excellent energy storage properties, with a maximum breakdown electric field of 432 kV / cm and a maximum energy storage density of 4.48 J / cm 3 .

[0047] In the present invention, a solid phase method is used to prepare a sodium niobate-based ceramic material with a high energy storage and high entropy component solid solution, and the process flow is simple. The following is an exemplary description of the preparation method of the sodium niobate-based ceramic material provided by the present invention.

[0048] According to the chemical formula (1-x)NaNbO3-x(La 0.2 Nd 0.2 Sm 0.2 G 0.2 Bi 0.2 )(Mg 2 / 3 Nb 1 / 3 )O3, and the ingredients are calculated. The raw material powders include sodium carbonate, niobium pentoxide, lanthanum oxide, neodymium oxide, gadolinium oxide, samarium oxide, bismuth oxide and magnesium oxide; an electronic balance is used for weighing, and the weighing accuracy is 0.001g. Among them, the purity of sodium carbonate is 99.8%, the purity of niobium pentoxide is 99.93%, the purity of lanthanum oxide is 99.99%, the purity of neodymium oxide is 99.99%, the purity of gadolinium oxide is 99.99%, the purity of samarium oxide is 99.99%, the purity of bismuth oxide is 99.999%, and the purity of magnesium oxide is 99.99%.

[0049] The weighed raw material powders are mixed and put into a ball mill, and ball milled and mixed with zirconium oxide columns and anhydrous ethanol as the medium, and finally dried and calcined to obtain ceramic powder. The calcination temperature can be 850-950°C, and the time can be 4-5 hours. The particle size of the zirconium oxide balls used for ball milling is 6mm, and the size of the zirconium oxide columns is 10mm in diameter × 10mm in height, and the number of each is half.

[0050] The ceramic powder is put into a stirring mill, ground with small-size zirconium oxide balls (for example, the size of the zirconium oxide balls is 1 mm) and anhydrous ethanol as media, and dried to obtain a mixed powder.

[0051] The mixed powder and the binder are mixed evenly, ground and granulated, sieved and molded to obtain a ceramic green body. The binder is a polyvinyl alcohol aqueous solution with a concentration of 6-7wt.%, and the amount added is 5-7% of the mass of the ceramic powder. The sieve mesh can be 40 mesh.

[0052] The ceramic green body is subjected to molding and sintering to obtain a sodium niobate-based ceramic material. The molding temperature can be 800°C and the time can be 2 hours. The sintering temperature can be 1300-1320°C and the sintering time can be 2-3 hours. Preferably, the temperature is increased to 1300-1320°C at a heating rate of 2°C / min at room temperature and kept at this temperature for 2 hours.

[0053] The sodium niobate-based ceramic material with a high-energy storage and high-entropy component solid solution is processed into a required size, and an energy storage ceramic element is obtained after the surface is coated with electrodes.

[0054] In the present invention, the obtained sodium niobate-based ceramic material has a high energy storage density (>4J / cm 3 ) and energy storage efficiency (>80%), suitable for the preparation and application of multilayer capacitors.

[0055] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0056] Example 1

[0057] (1) According to the molecular formula (1-x) NaNbO3-x(La 0.2 Nd 0.2 Sm 0.2 G 0.2 Bi 0.2 )(Mg 2 / 3 Nb 1 / 3)O3(x=0.05) is used for ingredient calculation. The raw materials used include: sodium carbonate with a purity of 99.8% and a molecular weight of 84.007; niobium pentoxide with a purity of 99.93% and a molecular weight of 265.810; lanthanum oxide with a purity of 99.99% and a molecular weight of 325.809; neodymium oxide with a purity of 99.99% and a molecular weight of 336.482; gadolinium oxide with a purity of 99.99% and a molecular weight of 362.498; samarium oxide with a purity of 99.99% and a molecular weight of 348.72; bismuth oxide with a purity of 99.999% and a molecular weight of 465.959; magnesium oxide with a purity of 99.99% and a molecular weight of 40.304. An electronic balance is used for weighing, and the weighing accuracy is 0.001g;

[0058] (2) The weighed raw materials are mixed and placed in a nylon can, and anhydrous ethanol is added to the can to a level not higher than 2 / 3 of the can height. The nylon can is placed on a planetary ball mill with zirconium oxide balls and zirconium oxide columns as the medium and mixed for 6 hours (the zirconium oxide balls used have a particle size of 6 mm and the zirconium oxide columns have a diameter of 10 mm × a height of 10 mm, and the number of each is half); then the mixture is poured out and dried in a baking oven, and then sieved with a 40-mesh nylon sieve, and the sieved mixed powder is pressed into a cylinder with a size of 15 mm in diameter × 2 mm in height on a press; the mixture is synthesized at 900° C. for 5 hours in an atmospheric atmosphere, and then crushed through a 40-mesh sieve to obtain a ceramic powder;

[0059] (3) grinding the obtained ceramic powder in a stirred mill using zirconium oxide balls with a diameter of 1 mm and anhydrous ethanol as a medium for 6 hours, and drying in a baking oven to obtain a mixed powder;

[0060] (4) Adding a 7 wt.% polyvinyl alcohol aqueous solution to the obtained mixed powder, the amount of polyvinyl alcohol aqueous solution added is 6.5% of the mass of the ceramic powder. Then granulate evenly, pass through a 40-mesh sieve, and mold to obtain a small cylinder with a size of 13 mm in diameter and 1 mm in height, and then perform plastic removal;

[0061] (5) The obtained green body after plastic removal was sintered in an alumina crucible at a sintering temperature of 1320° C. for 2 hours. After naturally cooling to room temperature, the sample was taken out to obtain a sodium niobate-based ceramic material.

[0062] The sodium niobate-based ceramic material prepared in Example 1 was subjected to an X-ray diffraction test. Figure 1 The X-ray diffraction diagram of Example 1 is shown. It can be seen that the ceramic obtained in Example 1 has no impurities. The surface morphology of the ceramic was taken after the chrome film was plated. Figure 2 The surface morphology of Example 1 is shown. It can be seen from the figure that the ceramic surface is dense. The ceramic is ground and polished on both sides, and silver electrodes are plated to test the electrical properties. Figure 6The dielectric temperature spectrum of Example 3 is shown. It can be seen from the figure that its dielectric constant changes little with temperature, that is, it has good temperature stability. Fig.10 The unipolar hysteresis loop of Example 1 is shown. It can be seen from the figure that the breakdown field strength of the ceramic is 298 kV / cm and the energy storage density is 2.78 J / cm 3 , the energy storage efficiency is 75.7%.

[0063] Example 2

[0064] Except that the value of x in step (1) is x=0.07, the preparation process of Example 2 is exactly the same as that of Example 1, except that the sintering temperature is 1300°C.

[0065] The sodium niobate-based ceramic material prepared in Example 2 was subjected to an X-ray diffraction test. Figure 1 The X-ray diffraction diagram of Example 2 is shown. It can be seen that the ceramic obtained in Example 2 has no impurities. The surface morphology of the ceramic was taken after the chrome film was plated. Figure 3 The surface morphology of Example 2 is shown. It can be seen from the figure that the ceramic surface is dense. The ceramic is ground and polished on both sides, and silver electrodes are plated to test the electrical properties. Figure 7 The dielectric temperature spectrum of Example 2 is shown. Fig.11 The unipolar hysteresis loop of Example 2 is shown. It can be seen from the figure that the breakdown field strength of the ceramic is 432 kV / cm and the energy storage density is 4.48 J / cm 3 , the energy storage efficiency is 88.2%. Fig.15 The unipolar hysteresis loops of Example 2 at different frequencies are shown. It can be seen from the figure that the energy storage density of the ceramic exhibits excellent frequency stability (2.52 J / cm 3 -2.68J / cm 3 ) Fig.17 The unipolar hysteresis loops of Example 2 at different cycle numbers are shown. It can be seen from the figure that the ceramic has a high conductivity at cycle numbers 1-10 under an electric field of 300 kV / cm. 7 Its energy storage density shows excellent fatigue resistance (2.56J / cm 3 -2.62J / cm 3 ).

[0066] Example 3

[0067] Except for the different value of x=0.03 in step (1), the preparation process of Example 3 is exactly the same as that of Example 1.

[0068] The sodium niobate-based ceramic material prepared in Example 3 was subjected to X-ray diffraction test. Figure 1 The X-ray diffraction pattern of Example 3 is shown. It can be seen that the obtained ceramic of Example has no impurity phase. Figure 4 The surface morphology of Example 3 is shown. It can be seen from the figure that the ceramic surface is dense. The ceramic is ground and polished on both sides, and silver electrodes are plated to test the electrical properties. Figure 8 The dielectric temperature spectrum of Example 3 is shown. It can be seen from the figure that its dielectric constant changes with temperature, that is, it has poor temperature stability. Fig.12 The unipolar hysteresis loop of Example 3 is shown. It can be seen from the figure that the breakdown field strength of the ceramic is 299 kV / cm and the energy storage density is 1.79 J / cm 3 , the energy storage efficiency is 24.5%.

[0069] Example 4

[0070] Except for the different value of x=0.09 in step (1), the preparation process of Example 4 is exactly the same as that of Example 1, except that the sintering temperature is 1300°C.

[0071] The sodium niobate-based ceramic material prepared in Example 4 was subjected to X-ray diffraction test. Figure 1 The X-ray diffraction pattern of Example 4 is shown. It can be seen that the obtained ceramic of Example has no impurity phase. Figure 5 The surface morphology of Example 4 is shown. It can be seen from the figure that the ceramic surface is dense. The ceramic is ground and polished on both sides, and silver electrodes are plated to test the electrical properties. Fig. 9 The dielectric temperature spectrum of Example 4 is shown. Fig.13 The unipolar hysteresis loop of Example 4 is shown. It can be seen from the figure that the breakdown field strength of the ceramic is 249 kV / cm and the energy storage density is 1.62 J / cm 3 , the energy storage efficiency is 86.2%.

[0072] The dielectric temperature spectra of Examples 1-4 of the present invention are as follows: Figure 6-9 As shown in the figure, as the high entropy component (La 0.2 Nd 0.2 Sm 0.2 G 0.2 Bi 0.2 )(Mg 2 / 3 Nb 1 / 3 )With the addition of O3, the dielectric peak moves toward the low temperature direction, gradually moves to below -120℃, and frequency dispersion phenomenon occurs.

[0073] The unipolar hysteresis loop of Example 1-2 of the present invention is as follows Figure 10-11 As shown, the breakdown electric fields of Example 1 and Example 2 are 298 kV / cm and 432 kV / cm respectively, and the maximum energy storage density is 2.78 J / cm 3 and 4.48 J / cm 3 , all greater than 2J / cm 3 .

[0074] The unipolar hysteresis loops of Examples 3-4 of the present invention are as follows: Figure 12-13 As shown, the breakdown electric fields of Example 3 and Example 4 are 248 kV / cm and 249 kV / cm respectively, and the maximum energy storage density is 1.79 J / cm 3 and 1.66 J / cm 3 It can be seen that the energy storage density of Examples 3-4 is less than 2 J / cm 3 .

[0075] The energy storage density variation curves of Examples 1-4 of the present invention are as follows: Fig.14 As shown in the figure, it can be seen that too low and too high (La 0.2 Nd 0.2 Sm 0.2 G 0.2 Bi 0.2 )(Mg 2 / 3 Nb 1 / 3 The energy storage density of the sodium niobate-based ceramics in Examples 3-4 with low O3 content is significantly weaker than that of the ceramics with moderate O3 content (La 0.2 Nd 0.2 Sm 0.2 G 0.2 Bi 0.2 )(Mg 2 / 3 Nb 1 / 3 ) The energy storage density of the sodium niobate-based ceramics in Example 1-2 with solid solution of 2O3. It can be seen that the design of NN-based high-entropy ceramic materials can achieve high energy storage characteristics, and the content of high-entropy components has a certain moderate range.

[0076] Table 1 shows the composition and properties of the sodium niobate-based ceramic material prepared by the present invention:

[0077] x Breakdown electric field Energy storage density Energy storage efficiency / % Example 1 0.05 298kV / cm <![CDATA[2.78J / cm 3 ]]> 75.7% Example 2 0.07 432kV / cm <![CDATA[4.48J / cm 3 ]]> 88.2% Example 3 0.03 248kV / cm <![CDATA[1.79J / cm 3 ]]> 24.5% Example 4 0.09 249kV / cm <![CDATA[1.66J / cm 3 ]]> 86.2% .

Claims

1. A high energy storage sodium niobate-based high entropy ceramic material, characterized in that: The chemical formula of the high energy storage sodium niobate-based high entropy ceramic material is (1-x)NaNbO3-x(La 0.2 Nd 0.2 Sm 0.2 G 0.2 Bi 0.2 )(Mg 2 / 3 Nb 1 / 3 )O3; wherein, 0.01≤x≤0.09; Sodium carbonate powder, niobium pentoxide powder, lanthanum oxide powder, neodymium oxide powder, gadolinium oxide powder, samarium oxide powder, bismuth oxide powder and magnesium oxide powder were selected as raw materials, and the chemical formula was (1-x)NaNbO3-x(La 0.2 Nd 0.2 Sm 0.2 G 0.2 Bi 0.2 )(Mg 2 / 3 Nb 1 / 3 )O3 is weighed and mixed, and then calcined to obtain ceramic powder; the obtained ceramic powder is mixed, and then a binder is added and granulated, sieved and molded to obtain a ceramic green body; the obtained ceramic green body is molded and sintered at 1300-1320°C for 2-3 hours to obtain a high energy storage sodium niobate-based high entropy ceramic material.

2. The high energy storage sodium niobate-based high entropy ceramic material according to claim 1, characterized in that: 0.03≤x≤0.09。 3. The high energy storage sodium niobate-based high entropy ceramic material according to claim 1 or 2, characterized in that: The breakdown electric field of the high energy storage sodium niobate-based high entropy ceramic material is 248 to 432 kV / cm; The energy storage efficiency of the high energy storage sodium niobate-based high entropy ceramic material is 24.5-88.2%; The energy storage density of the high energy storage sodium niobate-based high entropy ceramic material is 1.66-4.48 J / cm 3 .

4. The high energy storage sodium niobate-based high entropy ceramic material according to claim 3, characterized in that: The breakdown electric field of the high energy storage sodium niobate-based high entropy ceramic material is 300-432 kV / cm; The energy storage density of the high energy storage sodium niobate-based high entropy ceramic material is 2.78-4.48 J / cm 3 .

5. A method for preparing a high energy storage sodium niobate-based high entropy ceramic material according to any one of claims 1 to 4, characterized in that: include: (1) Sodium carbonate powder, niobium pentoxide powder, lanthanum oxide powder, neodymium oxide powder, gadolinium oxide powder, samarium oxide powder, bismuth oxide powder and magnesium oxide powder are selected as raw materials and the chemical formula is (1-x)NaNbO3-x(La 0.2 Nd 0.2 Sm 0.2 G 0.2 Bi 0.2 )(Mg 2 / 3 Nb 1 / 3 )O3 is weighed and mixed, and then calcined to obtain ceramic powder; (2) mixing the obtained ceramic powders, adding a binder, and granulating, sieving and molding to obtain a ceramic green body; (3) After the obtained ceramic green body is molded, it is sintered at 1300-1320° C. for 2-3 hours to obtain a high energy storage sodium niobate-based high entropy ceramic material.

6. The preparation method according to claim 5, characterized in that: In step (1), the mixing method is ball milling; the rotation speed of the ball milling is 200 to 240 revolutions per minute, and the time is 4 to 6 hours.

7. The preparation method according to claim 5, characterized in that: In step (1), the calcination temperature is 850-950° C. and the calcination time is 4-5 hours.

8. The preparation method according to claim 5, characterized in that: In step (2), the binder is a polyvinyl alcohol aqueous solution with a concentration of 6 to 7 wt.%; the amount of the binder added is 6 to 7 wt.% of the mass of the ceramic powder; and the sieve is 40 mesh.

9. The preparation method according to claim 5, characterized in that: In step (3), the temperature of the plastic removal is 750-850°C and the time is 2-3 hours; The heating rate of the sintering is 1-3°C / min.

10. The preparation method according to claim 9, characterized in that: The temperature of the plastic removal is 800°C and the time is 2 hours; The heating rate of the sintering is 2°C / min.

11. An energy storage ceramic element, comprising: The high energy storage sodium niobate-based high entropy ceramic material according to any one of claims 1 to 4, and the electrodes distributed on the surface of the sodium niobate-based ceramic material.

12. Use of the high energy storage sodium niobate-based high entropy ceramic material according to any one of claims 1 to 4 in a multilayer ceramic capacitor.

Citation Information

Patent Citations

  • Lead-free sodium niobate-based antiferroelectric ceramic with high saturated polarization and low residual polarization and preparation method thereof

    CN109809815A

  • Ceramic material integrating high energy storage density and efficiency, and preparation method thereof

    CN110204335A

  • High-energy-storage high-entropy-based lead-free X7R type ceramic material and preparation method thereof

    CN114956809A

  • High-entropy perovskite oxide doped ceramic, preparation method and application thereof

    CN115991599A

  • Sodium bismuth titanate-based high-entropy ceramic material with high energy storage characteristic as well as preparation method and application of sodium bismuth titanate-based high-entropy ceramic material

    CN116082034A